In vitro and in vivo survivality of gdhA derivative Pasteurella multocida B:2 - Oslan, Siti Nur Hazwani; Saad, Mohd Zamri; Mohamad, Rosfarizan; Bejo, Siti Khairani (Malaysian Society for Microbiology, 2014)
Aims: This study was carried out to determine the in vitro and in vivo survival pattern and period for the newly created gdhA derivative Pasteurella multocida B:2. Methodology and results: For the in vitro study, the gdhA derivative Pasteurella multocida B:2 was cultured in BHI and stored at 4°C and at room temperature (27°C). This was followed by determination of the colony-forming unit (CFU)/ mL at weekly intervals. When kept at 4 °C, the bacterial concentration (CFU/mL) showed insignificant (p> 0.05) weekly reduction until week 3. By week 4, the concentration was less than 102 CFU/mL. In the in vivo study, the derivative was injected intraperitoneal into a group of mice and compared with the group injected intraperitoneal with wild-type P. multocida B:2 and another control group injected with PBS. It was found that the gdhA derivative P. multocida B:2 remained intact for a period of 8 h, lost its kanamycin casette after the 8-h period but remained avirulent throughout the 96 h study period when none of the mice died. On the other hand, all mice that were exposed to the wild-type P. multocida B:2 were dead within 24 h post-injection. Conclusion, significance and impact study: The gdhA derivative P. multocida B:2 seemed to survive better when kept at 4°C and survived in the host for at least 4 days without returning the virulency. These are important since this strain can be used as live vaccine in animals with minimal possibility of returning back to virulent strain while the live vaccine can be stored at 4°C for at least 4 weeks.